Recent Development in Carbohydrate Based Anti-cancer Vaccines - Yin, Zhaojun (2012)
The development of carbohydrate based anti-cancer vaccines is of high current interests. Herein, the latest development in this exciting field is reviewed. After a general introduction about tumor associated carbohydrate antigens and immune responses, the review is focused on the various strategies that have been developed to enhance the immunogenecity of these antigens. The results from animal studies and clinical trials are presented.